2015
DOI: 10.1158/1078-0432.ccr-14-1566
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Validation of Reciprocal microRNA–mRNA Pairings in African American Prostate Cancer Disparities

Abstract: Purpose African Americans (AA) exhibit higher rates of prostate cancer (PCa) incidence and mortality compared to European American (EA) men. In addition to socioeconomic influences, biological factors are believed to play a critical role in PCa disparities. We investigated whether population-specific and -enriched miRNA-mRNA interactions might contribute to PCa disparities. Experimental Design Integrative genomics was employed, combining miRNA and mRNA profiling, miRNA target prediction, pathway analysis and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 50 publications
8
88
2
Order By: Relevance
“…We observed that MCL1 mRNA is elevated in AAHT compared with AANT and WHT, and decreased in WHT compared with WNT. Consistent with our findings in AAs, male AA prostate cancer patients have higher levels of MCL1 mRNA and protein compared to white males35. That study also identified miR-133a as a negative regulator of MCL1 35.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that MCL1 mRNA is elevated in AAHT compared with AANT and WHT, and decreased in WHT compared with WNT. Consistent with our findings in AAs, male AA prostate cancer patients have higher levels of MCL1 mRNA and protein compared to white males35. That study also identified miR-133a as a negative regulator of MCL1 35.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings in AAs, male AA prostate cancer patients have higher levels of MCL1 mRNA and protein compared to white males35. That study also identified miR-133a as a negative regulator of MCL1 35. miR-133a has previously been associated with hypertension17; however, miR-133a expression was not differentially-expressed in our cohort, suggesting that additional regulatory factors (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Computational pathway analysis suggested that miRNA–mRNA pairs predict the enhanced activation of EGFR–PI3K–AKT signaling in AA compared with EA cancers. Loss of function of these miRNA–mRNA pairs in AA prostate cancer cells reduced their proliferation, aggressiveness and increased docetaxel-induced cytotoxicity, while their converse manipulation in EA cell lines enhanced their aggressive potential (41). …”
Section: Molecular Bases Of Prostate Cancer Racial Disparitiesmentioning
confidence: 99%
“…Possible mechanisms that could drive differences in AS events include differential expression of trans -acting splicing factors47 and/or single-nucleotide polymorphisms in cis -acting splicing elements of alternatively spliced genes50. In fact, a number of splicing factor mRNAs appear to be overexpressed ( SRSF2 , SRSF7 ) in AA PCa compared with EA PCa910. Regarding the in-frame variants ( PIK3CD-L , FGFR3-L and TSC2-L ) detected in EA PCa, each conferred a less aggressive oncogenic phenotype compared with the corresponding in-frame variants detected in AA PCa ( PIK3CD-S , FGFR3-S and TSC2-S ).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro functional assays, including cell proliferation and invasion, were performed following siRNA transfections for 24 h. Cell proliferation and invasion assays were performed using 5-bromodeoxyuridine Cell Proliferation Assay kit (Calbiochem, Billerica, MA, USA) and the Matrigel Invasion Chambers (BD Biosciences, San Jose, CA, USA), respectively, as per the manufacturers’ protocol910.…”
Section: Methodsmentioning
confidence: 99%